PENGARUH OPTIMALISASI RUTE PELAYARAN TERHADAP EMISI GAS BUANG DI KAPAL KMP GILIMANUK II - Cicilia Kunti Dewi Cahyaningtyas; Rama Syahputra Simatupang; Intan Sianturi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of shipping route optimization on exhaust gas emissions on the KMP Gilimanuk II operating on the Ketapang–Gilimanuk route. The research method used is a quantitative approach utilizing primary and secondary data obtained from the Deck Log Book and Engine Log Book during the sea practice period. Data analysis was carried out by calculating fuel consumption and exhaust gas emissions using the Activity-Based Emission Calculation method. The results show that shipping routes influence the amount of fuel consumption and the level of exhaust gas emissions produced by the vessel. Differences in operational conditions such as travel distance, sailing duration, and ship maneuvering cause variations in fuel consumption and emissions on each route. A comparison between Route 3 and Route 19, which have the same sailing time (16 hours), shows that Route 19 produces higher emissions of 2,099.39 kg CO₂e compared to Route 3 which produces 1,994.30 kg CO₂e.Based on these findings, it can be concluded that optimizing shipping routes plays an important role in improving fuel efficiency and reducing ship exhaust gas emissions. Optimization efforts can be carried out through selecting more efficient sailing routes, regulating ship speed at an economical level, and improving operational management of shipping activities.